Use of xenograft compared to synthetic dermal substitute made of nanocellulose in patients with deep second-degree thermal burns, January 2022–July 2023 - Chau Ramos, Enrique Antonio (2025)
Objective: To compare scar formation between regenerated nanocellulose dermal substitutes and xenografts in patients with deep second-degree thermal burns. Materials and methods: A comparative, interventional, analytical, prospective and longitudinal study was conducted. We present the report of 60 cases evaluated in a private clinic in Lima, Peru, between January 2022 and July 2023. Patients aged 1 to 60 years without comorbidities were evaluated for scar formation from deep second-degree thermal burns within the first 24 hours of the accident. Both dermal substitutes were used in all patients. The study was authorized with informed consent. Results: An evaluation was conducted at 90 days, showing better scar formation with the synthetic dermal substitute made of nanocellulose compared to the xenograft. The results were evaluated using the Vancouver Scar Scale (VSS) (vascularization, pigmentation, pliability and height) and showed that the synthetic dermal substitute made of nanocelullose had less redness and greater elasticity, which were the most favorable indicators. The importance of the study lies in evaluating the quality of scar formation with the use of two treatments for deep second-degree burns. Conclusions: It was evident that the synthetic dermal substitute made of nanocellulose is an important alternative that favors the quality of scar formation in burned areas. It has proved to be more efficient than xenograft when evaluated and compared across its four parameters using the VSS, an international tool for wound healing evaluation. This efficient alternative for the treatment of second-degree burns promotes a better scar formation process, providing an adequate environment for healing under improved conditions.